Aqueous tape casting technique for the fabrication of Sc0.1Ce0·01Zr0·89O2+Δ ceramic for electrolyte-supported solid oxide fuel cell - Zhou, Juan (2020)
Despite some the advantages of the solid oxide fuel cell (SOFC), one of the greatest challenges that hinders the SOFC from rising to dominance in the field of power generation is its high fabrication cost. As a solution, the tape casting process has been widely used to fabricate low-cost, uniform and thin SOFC electrolytes. Compared to organic-based tape casting, aqueous-based tape casting is a much more environmentally friendly technique. In this work, a large-area electrolyte-supported solid oxide fuel cell was fabricated by this technique together with sintering. A 10 cm × 10 cm and 0.17 mm thick supported Sc0.1Ce0·01Zr0·89O2+△ (SSZ) electrolyte was obtained with good flatness, low ohmic resistance and high open-circuit voltage.